Roadmap to Sustainable Textiles and Clothing: Regulatory Aspects and Sustainability Standards of Textiles and the Clothing Supply Chain - Muthu, Subramanian Senthilkannan (Springer, 2015)
This book covers the elements involved in achieving sustainability in textiles and clothing sector. The chapters covered in three volumes of this series title cover all the distinctive areas earmarked for achieving sustainable development in textiles and clothing industry. This third volume highlights the areas pertaining to the regulatory aspects and sustainability standards applicable to textiles and clothing supply chain. There are various standards earmarked for measuring the environmental impacts and sustainability of textile products. There are also plenty of certification schemes available along with the index systems applicable to textile sector. Brands and manufactures are also venturing into new developments to achieve sustainable development in textile sector. This third volume addresses all these important aspects.